Оптически прозрачная керамика (обзор); Стекло и керамика; № 4 - Качаев А. А. Артём Алексеевич; Гращенков Д. В. Денис Вячеславович; Лебедева Ю. Е. Юлия Евгеньевна; Солнцев С. С. Сергей Станиславович; Хасанов О. Л. Олег Леонидович (Стеклокерамические материалы, 2016)
Заглавие с экрана